1969
DOI: 10.1104/pp.44.9.1335
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Respiratory Inhibitors on NADH, Succinate and Malate Oxidation in Corn Mitochondria

Abstract: The effect- Previous stttdies with plant mitochondria have -shown many similarities with animal mitochondria regarding substrates which are oxidized as well as the action of respiratory chain inhibitors (4,24,27,31). One exception is the capacity of plant mitochondria to ox.idize extramitochondrial NADH (2, 5,12,22,23,25,26). Animal mitochondria only slowly oxidize or lack the capacity to oxidize externally added NADH (3, 9, 13, 29, 36) unless cytochrome c is added to the reaction mix or the mitochondria are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
25
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 37 publications
8
25
0
Order By: Relevance
“…3). These results support those of others (8,15,19,26) (Fig. 3A); Cyt c alone had no such effect on the inhibited malate oxidation (Fig.…”
Section: Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…3). These results support those of others (8,15,19,26) (Fig. 3A); Cyt c alone had no such effect on the inhibited malate oxidation (Fig.…”
Section: Methodssupporting
confidence: 82%
“…Douce et al. (8) and Moreau and Lance (16) have recently confirmed earlier suggestions (7, 26,27) that an additional pathway of NADH oxidation exists on the outer mitochondrial membrane, similar to that associated with rat liver mitochondria (19).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…7). NADH oxidation via this enzyme is inhibited by both rotenone and antimycin A. and coupled to three sites of ATP formation (10,17). Pathways (a) and (b) above are available to exogenous NADH, while pathwvay (c) is accessible only to NADH generated within the matrix, i.e.…”
mentioning
confidence: 99%
“…Table III shows that the promotion of ADP accumulation occurs with both AdN translocase inhibitors, making it unlikely that a side effect of C-ATR is responsible. In the course of other investigations we have found that rotenone will promote the phosphate swelling and 32Pi uptake energized by NADH oxidation (oxidation of exogenous NADH by corn mitochondria is not inhibited by rotenone, and can even be promoted slightly [21]). Rotenone also proves to promote ADP accumulation over the level of the oligomycin control (Table III) The rate of AMP and ATP exchange was partially inhibited by C-ATR, but not that of ADP (Fig.…”
Section: Methodsmentioning
confidence: 99%